Odpowiedź :
Odpowiedź:
2-(x-5)(1-x)=[tex]x^{2}[/tex]-7
2-x+[tex]x^{2}[/tex]+5-5x=[tex]x^{2}[/tex]
7-6x+[tex]x^{2}[/tex]=[tex]x^{2}[/tex]-7/ -[tex]x^{2}[/tex]
7-6x=7 /-7
-6x=0
Szczegółowe wyjaśnienie:
[tex]2-(x-5)(1-x)= x^2 - 7[/tex]
[tex]2 - (x - x^2 - 5 + 5x) = x^2 - 7[/tex]
[tex]2 - (6x - x^2 - 5) = x^2 - 7[/tex]
[tex]2 - 6x + x^2 + 5x = x^2 - 7[/tex]
[tex]2 - 6x + 5 = 7[/tex]
[tex]7 - 6x = -7[/tex]
-6x = -7 - 7
-6x = -14 /:(-6)
x = [tex]\frac{14}{6}[/tex]
x = [tex]\frac{7}{3}[/tex]
x = [tex]2\frac{1}{3}[/tex]